Push-out bond strength and SEM evaluation of a new bonding approach into the root canal (Journal of Applied Oral Science, 2012)
OBJECTIVE: This study evaluated the performance of different adhesive systems in fiber post placement aiming to clarify the influence of different hydrophobic experimental blend adhesives, and of one commercially available adhesive on the frictional retention during a luting procedure. MATERIAL AND METHODS: One luting agent (70 Wt% BisGMA, 28.5% TEGDMA; 1.5% p-tolyldiethanolamine) to cement fiber posts into root canals was applied with 4 different adhesive combinations: Group 1: The etched roots were rinsed with water for 30 s to remove the phosphoric acid, then rinsed with 99.6% ethanol for 30 s, and blotdried. A trial adhesive (base to catalyst on a 1:1 ratio) was used with an experimental luting agent (35% Bis-GMA, 14.37% TeGDMA, 0.5% eDMAB, 0.13% CQ); Group 2: A trial adhesive (base to catalyst on a 1:2 ratio) was luted as in Group 1; Group 3: One-Step Plus (OSP, Bisco Inc.) following the ethanol bonding technique in combination with the luting agent as in Group 1; Group 4: OSP strictly following the manufacturer's instructions using the luting agent as in Group 1. The groups were challenged with push-out tests. Posted root slices were loaded until post segment extrusion in the apical-coronal direction. Failure modes were analyzed under scanning electron microscopy. RESULTS: Push-out strength was not significantly influenced by the luting agent (p>;0.05). No statistically significant differences among the tested groups were found as Group 1 (exp 1 - ethanol-wet bonding technique)=Group 2 (exp 2 - ethanol-wet bonding technique)=Group 3 (OSP - ethanol-wet bonding technique)=Group 4 (control, OSP - water-wet bonding technique) (p>;0.05). The dominating failure modes in all the groups were cohesive/adhesive failures, which were predominantly observed on the post/luting agent interface. CONCLUSIONS: The results of this study support the hypothesis that the proposal to replace water with ethanol to bond fiber posts to the root canal using highly hydrophobic resin is plausible, but this seems to be more the proof of a concept than a clinically applicable procedure.